Lemonade in winter : a book about two kids counting money - Jenkins, Emily, 1967- (Schwartz & Wade Books, 2012)
Pauline and her brother John-John set up a stand to sell lemonade, limeade, and lemon-limeade one cold, wintry day, then try to attract customers as Pauline adds up their earnings.